Hard TiAlSiN composite coating with low internal stress and preparation method
By using a thick AlTiN layer and controlling the Al content in the TiAlSiN coating, combined with low-energy ion bombardment and vacuum annealing, the problem of large internal stress in the TiAlSiN coating was solved, and high hardness, low internal stress and excellent tribological properties were achieved. coating.
Patent Information
- Application Number
- CN202411450336.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-24
AI Technical Summary
The existing TiAlSiN coating has a large internal stress, resulting in a decrease in hardness and insufficient toughness, which cannot meet the application needs of high temperature and high load.
A thicker AlTiN layer is used as the transition layer, and the Al atom content in the TiAlSiN layer is controlled within the solid solubility of the c-TiN lattice to avoid the precipitation of the h-AlN phase. At the same time, the internal stress of the coating is reduced through low-energy ion bombardment and vacuum annealing.
The hard tialsin composite coating of low internal stress is achieved, maintaining high hardness and increasing toughness, has excellent friction learning performance and the effect of extending the service life of the workpiece.
Smart Images

Figure CN119351943A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of tool and die modification, and relates to a hard TiAlSiN composite coating with low internal stress and a preparation method thereof. Background Art
[0002] Physical vapor deposition coating technology has the characteristics of being green and pollution-free, and is widely used in aerospace, mechanical processing, and automotive parts as a protective layer. Among them, Al atoms are dissolved into the TiN lattice to form a ternary TiAlN coating, which is oxidized at high temperature to form a dense Al2O3, effectively raising the anti-oxidation temperature of the coating to 800℃. The formation of (Ti,Al)N solid solution also improves the hardness and wear resistance of the coating. However, its performance is affected by the Al doping content. The research results show that when the Al content is lower than 67%, the coating phase structure exists in the c-Ti(Al)N phase. As the Al content increases, the hardness, oxidation resistance and mechanical properties of the coating gradually increase. When the Al atomic content exceeds 67%, the coating is mainly composed of c-TiN and h-AlN phases, and the comprehensive performance gradually decreases. In addition, with the widespread promotion of high-speed dry cutting mode and the application of difficult-to-process materials such as high-temperature alloys, coated workpieces are often used in high-temperature (greater than 1000℃) and high-load occasions, and the ternary TiAlN coating can no longer meet the demand.
[0003] In order to further improve the oxidation resistance, mechanical properties and tribological properties of TiAlN coatings, researchers doped Si, Cr, V and B elements into TiAlN coatings to form quaternary TiAlXN (X represents doping elements) coatings, and explored the effects of doping element content and type on the performance of quaternary coatings. Among them, the TiAlSiN coating formed by Si doping has been widely studied due to its low surface chemical activity, high hardness and good thermal stability. The amorphous structure formed by Si element doping can effectively improve the oxidation resistance and wear resistance of TiAlN coatings, but the amorphous structure will hinder the growth of TiAlN nanocrystals, resulting in an increase in grain boundaries and increased internal stress, which limits its further application. Current studies have shown that by introducing a modulation layer and designing a multilayer structure, the internal stress of the TiAlSiN coating can be effectively reduced, but the hardness decreases significantly, and it is extremely difficult to obtain a multilayer TiAlSiN coating with excellent performance. The modulation period and modulation ratio required are extremely difficult. Therefore, it is very urgent and of scientific value to explore new processes to obtain TiAlSiN coatings with high hardness and low internal stress.
[0004] Patent CN107227441A discloses a method for preparing a TiAlSiN coating based on the reactive sputtering hysteresis effect, including workpiece pretreatment, gas path cleaning, argon ion bombardment, deposition of a bonding layer Ti, deposition of a transition layer TiN, deposition of a functional layer TiAlSiN, cooling, and furnace removal. However, the patent mainly stabilizes the hysteresis deposition process by controlling the nitrogen flow rate to make it completely in a target poisoning state. Although it also includes workpiece treatment, ion etching before deposition, and a multilayer structure design, the deposited coating has a large internal stress and does not have the effect of making the TiAlSiN coating both hard and tough.
[0005] Patent CN115198229A discloses a multilayer ultra-low stress hard film with alternating layer-columnar microstructures and a preparation method thereof, wherein the hard film comprises n periodic coatings, wherein each of the periodic coatings comprises layered layers and columnar layers stacked in sequence from bottom to top, wherein the Me metal in the hard film can be selected from any one of Ti, Cr, TiAl, TiAlSi, CrAl, CrAlSi, and TiCrAlSi; the method comprises: obtaining an alloy substrate to be protected; surface cleaning the alloy substrate to be protected; using arc ion plating technology to alternately deposit on the substrate to form a multilayer hard film with alternating layer-columnar microstructures; and then using vacuum annealing technology to remove stress from the multilayer hard film with alternating layer-columnar microstructures to obtain a multilayer ultra-low stress hard film layer with alternating layer-columnar microstructures. This patent uses nano multilayer structure design and vacuum insulation treatment together. First of all, it is very unnecessary in the actual process. The design of the nano multilayer film itself consumes the hardness of the coating to reduce the internal stress of the coating, and further adopts vacuum insulation treatment, which further reduces the hardness of the coating, and seriously reduces the lifespan in actual application. It is also worth noting that this patent is to directly heat up the coating for insulation treatment after the coating deposition is completed, and direct heating will cause thermal stress. In addition, no etching is performed before insulation, and there is a high internal stress in the surface layer. Summary of the invention
[0006] The purpose of the present invention is to provide a hard TiAlSiN composite coating with low internal stress and a preparation method in order to overcome at least one defect of the above-mentioned prior art, such as large internal stress of the TiAlSiN coating. The present invention has low internal stress, maintains high hardness and has good toughness and excellent tribological properties.
[0007] The purpose of the present invention can be achieved by the following technical solutions:
[0008] One of the technical solutions of the present invention is to provide a hard TiAlSiN composite coating with low internal stress, the composite coating comprises a TiN primer layer, an AlTiN layer and a TiAlSiN layer sequentially deposited on the surface of a substrate, first cooled after deposition, then bombarded with low-energy ions, and then second cooled after vacuum annealing;
[0009] The vacuum annealing temperature is 450-480°C and the vacuum degree is 8×10 -4 ~3×10 -3 Pa, the holding time is 120-150min;
[0010] The secondary cooling rate is 2-6°C / min and the temperature is 50-350°C.
[0011] One of the technical solutions of the present invention is to provide a method for preparing the hard TiAlSiN composite coating with low internal stress, the method comprising the following steps:
[0012] S1. Matrix pretreatment,
[0013] Place the substrate in a cleaning agent for ultrasonic vibration and blow dry;
[0014] S2. Preparation of hard composite coating,
[0015] S2.1, substrate etching,
[0016] Heating, vacuuming, introducing the gas to be ionized, and etching the substrate;
[0017] S2.2, TiN base deposition,
[0018] Heating, vacuuming, introducing nitrogen, connecting the Ti target, and depositing the TiN base layer;
[0019] S2.3, AlTiN layer deposition,
[0020] Heating, vacuuming, introducing nitrogen, connecting AlTi target, and depositing AlTiN layer;
[0021] S2.4, TiAlSiN layer deposition,
[0022] Heating, vacuuming, introducing nitrogen, connecting AlTi target, connecting TiSi target, and depositing TiAlSiN layer;
[0023] S3, initial cooling;
[0024] S4, low energy ion bombardment,
[0025] Heating, vacuuming, introducing the gas to be ionized, and ion bombarding the coating;
[0026] S5, vacuum annealing,
[0027] S6, secondary cooling,
[0028] A hard TiAlSiN composite coating with low internal stress is obtained by performing two-stage cooling at a high rate first and then a low rate.
[0029] Furthermore, in step S1, the cleaning agent is selected from one or more of ethanol, water, and acetone;
[0030] The frequency of ultrasonic oscillation is 80-150kHz, and the time is 15-20min.
[0031] As a preferred technical solution, dry air or nitrogen is used for drying in step S1.
[0032] As a preferred technical solution, in step S2, the purity of each element of the Ti target, the AlTi target and the TiSi target is greater than 99.98%.
[0033] Furthermore, the heating temperature in step S2.1 is 400-420°C.
[0034] The vacuum degree of vacuum pumping is 1×10 -3 ~3×10 -3 Pa,
[0035] The gas to be ionized is selected from one or more rare gases of argon, neon, and helium, and the flow rate of the gas to be ionized is 200 to 240 sccm.
[0036] The substrate bias voltage for etching is -680 to -650 V, and the etching time is 10 to 15 minutes.
[0037] Furthermore, the heating temperature in step S2.2 is 400-420°C.
[0038] The vacuum degree of vacuum pumping is 1~3Pa.
[0039] The flow rate of nitrogen is 180-220 sccm,
[0040] The current of Ti target is 140~160A,
[0041] The substrate bias voltage of the deposition is -140 to -120 V, and the thickness of the TiN base layer is 0.15 to 0.2 μm.
[0042] Furthermore, the heating temperature in step S2.3 is 400-420°C.
[0043] The vacuum degree of vacuum pumping is 1~3Pa.
[0044] The flow rate of nitrogen is 180-220 sccm,
[0045] AlTi target is made of Al0.67 Ti 0.33 Target, AlTi target current is 120 ~ 140A,
[0046] The substrate bias voltage of the deposition is -120 to -100 V, and the thickness of the AlTiN layer is 1.5 to 2 μm.
[0047] Furthermore, the heating temperature in step S2.4 is 400-420°C.
[0048] The vacuum degree of vacuum pumping is 1~3Pa.
[0049] The flow rate of nitrogen is 200~240sccm,
[0050] AlTi target is made of Al 0.67 Ti 0.33 Target, AlTi target current is 100 ~ 120A,
[0051] TiSi target uses Ti 0.8 Si 0.2 Target, TiSi target current is 120~140A,
[0052] The substrate bias voltage of the deposition is -120 to -100 V, and the thickness of the TiAlSiN layer is 1.1 to 1.5 μm.
[0053] Furthermore, the temperature of the initial cooling in step S3 is 80-100°C.
[0054] Furthermore, the heating temperature in step S4 is 450-480°C.
[0055] The vacuum degree of vacuum pumping is 8×10 -4 ~3×10 -3 Pa,
[0056] The gas to be ionized is selected from one or more rare gases of argon, neon, and helium, and the flow rate of the gas to be ionized is 200 to 240 sccm.
[0057] The bombardment substrate bias voltage is -220 to -180 V, and the time is 10 to 15 minutes.
[0058] Furthermore, in step S6, the first stage of the two-stage cooling has a cooling rate of 4-6°C / min and a temperature of 200-350°C.
[0059] The cooling rate of the second stage is 2-4°C / min and the temperature is 50-200°C.
[0060] Compared with the prior art, the present invention has the following beneficial effects:
[0061] (1) The present invention uses a thicker AlTiN layer, which helps to reduce the internal stress of the coating while improving the bearing capacity of the coating;
[0062] (2) The Al atom content in the AlTiN layer and the TiAlSiN layer of the present invention is within the solid solubility of the Al atom in the c-TiN lattice, and no h-AlN phase is precipitated, so that the coating maintains good mechanical properties. After the two layers of coating are composited, the hardness and wear resistance are further improved and the internal stress is reduced;
[0063] (3) The present invention uses low-energy (lower substrate bias) ion bombardment to restore defects generated during coating deposition, and can make the surface of the coating dense and reduce roughness, thereby improving the surface quality of the coating and facilitating the release of internal stress in the surface layer;
[0064] (4) The present invention adopts vacuum annealing of the coating by heating up and then cooling, which is beneficial to the recovery of defects, can further reduce the internal stress of the coating, obtain a hard coating with better mechanical properties, and greatly improve the service life of the coated workpiece. In addition, the slow cooling rate can inhibit lattice distortion, which is beneficial to reducing internal stress and preventing the increase of internal stress.
[0065] (5) The present invention adopts multiple ways to reduce the internal stress of the coating, which is not easy to produce cracks during use. It improves toughness while maintaining high hardness and has excellent tribological properties, which is beneficial to improving the service life and use effect of the coated workpiece. BRIEF DESCRIPTION OF THE DRAWINGS
[0066] Figure 1 Schematic diagram of the structure of a hard TiAlSiN composite coating with low internal stress in an embodiment of the present invention;
[0067] Figure 2 A comparison chart of the friction coefficients of the composite coatings in the embodiments of the present invention and the comparative examples;
[0068] Figure 3 The figure is a comparison chart of the wear rate of the composite coating in the embodiment of the present invention and the comparative example.
[0069] Description of the markings in the figure:
[0070] 1—substrate, 2—TiN base layer, 3—AlTiN layer, 4—TiAlSiN layer. DETAILED DESCRIPTION
[0071] The present invention is described in detail below in conjunction with specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0072] Unless otherwise specified, the equipment used in the following examples are all conventional equipment in the art; the reagents used are all commercially available products or prepared by conventional methods in the art unless otherwise specified. Anything not described in detail in the following examples can be achieved by conventional experimental means in the art.
[0073] In this embodiment, the Ti target and Al 0.67 Ti 0.33 Target and Ti 0.8 Si 0.2 The purity of each element of the target was 99.99%.
[0074] Example:
[0075] A low internal stress hard TiAlSiN composite coating and a preparation method thereof, the specific steps are as follows:
[0076] S1, substrate 1 pretreatment,
[0077] The substrate 1 was placed in anhydrous ethanol and deionized water in turn and ultrasonically vibrated at a frequency of 110 kHz for 18 minutes, and then taken out and dried with dry air;
[0078] S2, such as Figure 1 As shown, the hard composite coating is prepared.
[0079] S2.1, substrate 1 etching,
[0080] Heated to 400°C, vacuumed to 2×10 -3 Pa, 200 sccm of argon was introduced, and the substrate was etched at a substrate bias of -650 V for 1 12 min;
[0081] S2.2, TiN base layer 2 deposition,
[0082] The temperature was maintained at 400° C., and when the vacuum was evacuated to 1 Pa, 180 sccm of nitrogen was introduced, and a current of 160 A was connected to the Ti target, and a 0.2 μm TiN base layer 2 was deposited at a substrate bias of -140 V;
[0083] S2.3, AlTiN layer 3 deposition,
[0084] Maintaining the temperature at 400°C, vacuum at 1Pa, nitrogen flow at 180sccm, Al 0.67 Ti 0.33 The target was connected to a 140A current, and a 2μm AlTiN layer 3 was deposited at a substrate bias of -120V;
[0085] S2.4, TiAlSiN layer 4 deposition,
[0086] Maintaining the temperature at 400°C and the vacuum at 1Pa, 200sccm of nitrogen was introduced. 0.67 Ti 0.33 The target is connected to a 120A current, Ti 0.8 Si 0.2 The target was connected to a 140A current, and a 1.5μm TiAlSiN layer 4 was deposited at a substrate bias of -120V;
[0087] S3, first cooling with the furnace to 80°C;
[0088] S4, low energy ion bombardment,
[0089] Heated to 480℃, vacuumed to 1×10 -3 Pa, 200 sccm of argon was introduced, and the coating was bombarded with ions for 12 min at a substrate bias of -200 V;
[0090] S5, vacuum annealing,
[0091] Maintain temperature at 480°C and vacuum at 1×10 -3 Pa, keep warm for 150min;
[0092] S6, secondary cooling,
[0093] The coating was cooled to 300°C at a rate of 5°C / min and then to 100°C at a rate of 3°C / min to obtain a hard TiAlSiN composite coating with low internal stress.
[0094] Comparative Example 1:
[0095] An AlTiN composite coating and a preparation method thereof are basically the same as the embodiment, except that in step S2, steps S2.1 to S2.3 are adopted, and steps S2.4 and S4 to S6 are not adopted.
[0096] Comparative Example 2:
[0097] A TiAlSiN composite coating and a preparation method thereof are basically the same as the embodiment, except that in step S2, steps S2.1, S2.2 and S2.4 are adopted, and steps S2.3, S4 to S6 are not adopted.
[0098] Comparative Example 3:
[0099] A TiAlSiN composite coating and a preparation method thereof are basically the same as those in the embodiment, except that steps S1 to S3 are taken and steps S4 to S6 are not taken.
[0100] Comparative Example 4:
[0101] A TiAlSiN composite coating and a preparation method thereof are basically the same as those in the embodiment, except that steps S1 to S4 are taken, and steps S5 and S6 are not taken.
[0102] Comparative Example 5:
[0103] A TiAlSiN composite coating and a preparation method thereof are basically the same as those in the embodiment, except that in step S6, the coating is cooled in one step to 100° C. at a rate of 10° C. / min.
[0104] 1. The hardness test of the above composite coating is as follows:
[0105] The nanohardness of the coating was tested and calculated using a nanoindenter. The continuous stiffness indentation mode was selected with a loading force of 15 mN. To ensure the accuracy of the coating hardness, the indentation depth did not exceed 1 / 10 of the coating thickness.
[0106] The hardness of the hard TiAlSiN composite coating with low internal stress in the embodiment is 41.214 GPa, and the hardness of the AlTiN composite coating in Comparative Example 1 is 31.425 GPa. Compared with the embodiment, Comparative Example 1 lacks the TiAlSiN layer 4 with higher hardness, and the AlTiN layer 3 itself has lower hardness, so the overall hardness is low;
[0107] The hardness of the TiAlSiN composite coating in Comparative Example 2 is 39.256 GPa. Compared with the embodiment, Comparative Example 2 lacks the AlTiN layer 3 as a transition layer, and the hardness of the coating is slightly reduced;
[0108] The average hardness of the TiAlSiN composite coating in Comparative Example 3 is 41.172 GPa. Compared with the embodiment, Comparative Example 3 lacks low-energy ion etching and secondary annealing treatment, and has no obvious effect on the hardness of the coating compared with the embodiment;
[0109] The hardness of the TiAlSiN composite coating in Comparative Example 4 is 42.378 GPa. Compared with the embodiment, Comparative Example 4 lacks secondary annealing treatment. Although the atoms on the surface of the coating are relaxed after low-energy ion etching, the internal atoms are not relaxed, which increases the mismatch between the outer layer and the inner layer, increases the internal stress of the coating, and slightly increases the hardness.
[0110] The hardness of the TiAlSiN composite coating in Comparative Example 5 is 43.516 GPa. Compared with the embodiment, the cooling speed of Comparative Example 5 is faster, and the atoms inside the coating are cooled before they are fully relaxed, which increases the thermal stress of the coating and increases the hardness of the coating.
[0111] In summary, the hardness of the coating in Comparative Example 1 is much lower than that of the other coatings, while the hardness of the coatings in Comparative Examples 2 to 5 is not much different from that in the embodiment.
[0112] 2. The stress test of the above composite coating is as follows:
[0113] The stress is calculated using the curvature method and the Stoney formula.
[0114] The Stoney formula is as follows:
[0115]
[0116] Among them, δ f is the internal stress of the coating, E s 、V s are the elastic modulus and Poisson’s ratio of the matrix 1, t s and t f is the thickness of the substrate 1 and the coating, and R is the radius of curvature of the substrate 1.
[0117] The internal stress of the hard TiAlSiN composite coating with low internal stress in the embodiment is -1.35 GPa, and the internal stress of the AlTiN composite coating in Comparative Example 1 is -3.18 GPa. Compared with the embodiment, although Comparative Example 1 lacks the TiAlSiN layer 4, resulting in a theoretical decrease in internal stress, it lacks low-energy ion etching and secondary annealing treatment, and the thermal stress generated inside the coating cannot be relaxed, so the internal stress of the coating is still relatively high;
[0118] The internal stress of the TiAlSiN composite coating in Comparative Example 2 is -4.65 GPa. Compared with the embodiment, Comparative Example 2 lacks the AlTiN layer 3 as a transition layer, so that the difference in thermal expansion coefficient between the TiAlSiN layer 4 and the TiN base layer 2 is larger, the lattice mismatch is large, the internal stress is higher, and the low-energy ion etching and secondary annealing treatment are lacking, the thermal stress generated inside the coating cannot be relaxed, and the internal stress of the coating is relatively high;
[0119] The internal stress of the TiAlSiN composite coating in Comparative Example 3 is -4.21 GPa. Compared with the embodiment, Comparative Example 3 lacks low-energy ion etching and secondary annealing treatment, and the thermal stress generated inside the coating cannot be relaxed, resulting in a high internal stress of the coating.
[0120] The internal stress of the TiAlSiN composite coating in Comparative Example 4 is -5.34 GPa. Compared with the embodiment, Comparative Example 4 lacks secondary annealing treatment. Although the atoms on the surface of the coating are relaxed after low-energy ion etching, the internal atoms are not relaxed, which increases the mismatch between the outer layer and the inner layer, and the internal stress of the coating increases.
[0121] The internal stress of the TiAlSiN composite coating in Comparative Example 5 is -5.12 GPa. Compared with the embodiment, the cooling speed of Comparative Example 5 is faster, and the atoms inside the coating are cooled before they are fully relaxed, which increases the thermal stress of the coating.
[0122] In summary, the low internal stress in the embodiment can be attributed to the following points:
[0123] The gradient multi-layer structure design is conducive to stress release through the interface movement between layers;
[0124] After the coating is completed, the coating is kept warm to restore the internal defects, which is conducive to stress release.
[0125] 3. The wear resistance test of the above composite coating is as follows:
[0126] The tribological properties of the coating were tested using a UMT-3 friction tester in an atmospheric environment. The friction mode was ball-disc type, a Si3N4 ceramic ball with a diameter of 9.5 mm was selected as the friction pair, the load was 15 N, the speed was 200 r / min, the wear spot diameter was 10 mm, and the friction time was 10 min.
[0127] The wear volume of the coating was measured using a white light interferometer, and the wear rate (Wearrate) of the coating was calculated using the formula W=V / FS, where W is the wear rate, V is the wear volume, F is the load, and S is the friction distance.
[0128] like Figure 2 As shown, the friction coefficient of the hard TiAlSiN composite coating with low internal stress in the embodiment is 0.32, the friction coefficient of the AlTiN composite coating in comparative example 1 is 0.51, the friction coefficient of the TiAlSiN composite coating in comparative example 2 is 0.43, the friction coefficient of the TiAlSiN composite coating in comparative example 3 is 0.4, the friction coefficient of the TiAlSiN composite coating in comparative example 4 is 0.45, and the friction coefficient of the TiAlSiN composite coating in comparative example 5 is 0.41.
[0129] In summary, the friction coefficient of the coating in Comparative Example 1 is the highest, which can be attributed to its lower hardness and larger Hertzian contact area between it and the friction pair;
[0130] The lowest friction coefficient of the coating in the embodiment can be attributed to its good toughness, while the internal stress of the coating in comparative examples 2 to 5 is high, and micro cracks are easily generated during the friction process, and the shear resistance of the friction ball increases along the grain boundary process, so that micro peeling occurs, resulting in a higher friction coefficient of the coating in comparative examples 2 to 5;
[0131] In particular, Example 4 lacks secondary annealing treatment. Although a thin layer of atoms on the coating surface relaxes after low-energy ion etching, the internal atoms cannot relax, resulting in an increased mismatch between the inner and outer layers. When subjected to external forces, it is easy to peel off, causing severe abrasive wear.
[0132] like Figure 3As shown in Figure 2, the wear rate of the hard TiAlSiN composite coating with low internal stress in the embodiment is 3.6×10 -5 mm 3 / N·m, the wear rate of the AlTiN composite coating in Comparative Example 1 is 8.7×10 -5 mm 3 / N·m, the wear rate of the TiAlSiN composite coating in Comparative Example 2 is 7.9×10 -5 mm 3 / N·m, the wear rate of the TiAlSiN composite coating in Comparative Example 3 is 7.2×10 -5 mm 3 / N·m, the wear rate of the TiAlSiN composite coating in Comparative Example 4 is 1.08×10 -4 mm 3 / N·m, the wear rate of the composite TiAlSiN coating in Comparative Example 5 is 6.5×10 -5 mm 3 / N·m.
[0133] In summary, the wear rate of the coating in the embodiment is the lowest, the wear rate of the coating in comparative example 4 is the highest, and the wear rate of the coating in comparative example 1 is second, which shows that the tribological properties of the coating are not only affected by the hardness, but also the toughness is very important. Only the coating with high hardness and low internal stress can obtain excellent tribological properties. At the same time, the wear rate results further prove that the embodiment has the best tribological properties.
[0134] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A hard TiAlSiN composite coating with low internal stress, characterized in that: The composite coating comprises a TiN base layer (2), an AlTiN layer (3) and a TiAlSiN layer (4) which are sequentially deposited on the surface of a substrate (1), and is cooled for the first time after deposition, and then bombarded with low-energy ions, and then vacuum annealed and cooled for the second time; The vacuum annealing temperature is 450-480°C and the vacuum degree is 8×10 -4 ~3×10 -3 Pa, the holding time is 120~150min; The secondary cooling rate is 2-6°C / min and the temperature is 50-350°C.
2. A method for preparing a hard TiAlSiN composite coating with low internal stress as claimed in claim 1, characterized in that: The method comprises the following steps: S1, substrate (1) pretreatment, The substrate (1) is placed in a cleaning agent for ultrasonic vibration and blown dry; S2. Preparation of hard composite coating, S2.1, substrate (1) etching, Heating, evacuating, introducing a gas to be ionized, and etching the substrate (1); S2.2, TiN base layer (2) deposition, Heating, evacuating, introducing nitrogen, connecting a Ti target, and depositing a TiN base layer (2); S2.3, AlTiN layer (3) deposition, Heating, evacuating, introducing nitrogen, connecting an AlTi target, and depositing an AlTiN layer (3); S2.4, TiAlSiN layer (4) is deposited, Heating, evacuating, introducing nitrogen, connecting an AlTi target, connecting a TiSi target, and depositing a TiAlSiN layer (4); S3, initial cooling; S4, low energy ion bombardment, Heating, vacuuming, introducing the gas to be ionized, and ion bombarding the coating; S5, vacuum annealing, S6, secondary cooling, A hard TiAlSiN composite coating with low internal stress is obtained by performing two-stage cooling at a high rate first and then a low rate.
3. The method for preparing a hard TiAlSiN composite coating with low internal stress according to claim 2, characterized in that: In step S1, the cleaning agent is selected from one or more of ethanol, water, and acetone; The frequency of ultrasonic oscillation is 80-150kHz, and the time is 15-20min.
4. The method for preparing a hard TiAlSiN composite coating with low internal stress according to claim 2, characterized in that: The heating temperature in step S2.1 is 400-420°C. The vacuum degree of vacuum pumping is 1×10 -3 ~3×10 -3 Pa, The gas to be ionized is selected from one or more rare gases of argon, neon, and helium, and the flow rate of the gas to be ionized is 200 to 240 sccm. The substrate bias voltage for etching is -680 to -650 V, and the etching time is 10 to 15 minutes.
5. The method for preparing a hard TiAlSiN composite coating with low internal stress according to claim 2, characterized in that: The heating temperature in step S2.2 is 400-420°C. The vacuum degree of vacuum pumping is 1~3Pa. The flow rate of nitrogen is 180-220 sccm, The current of Ti target is 140~160A, The substrate bias voltage during deposition is -140 to -120 V, and the thickness of the TiN base layer (2) is 0.15 to 0.2 μm.
6. The method for preparing a hard TiAlSiN composite coating with low internal stress according to claim 2, characterized in that: The heating temperature in step S2.3 is 400-420°C. The vacuum degree of vacuum pumping is 1~3Pa. The flow rate of nitrogen is 180-220 sccm, AlTi target is made of Al 0.67 Ti 0.33 Target, AlTi target current is 120 ~ 140A, The substrate bias voltage during deposition is -120 to -100 V, and the thickness of the AlTiN layer (3) is 1.5 to 2 μm.
7. The method for preparing a hard TiAlSiN composite coating with low internal stress according to claim 2, characterized in that: The heating temperature in step S2.4 is 400-420°C. The vacuum degree of vacuum pumping is 1~3Pa. The flow rate of nitrogen is 200~240sccm, AlTi target is made of Al 0.67 Ti 0.33 Target, AlTi target current is 100 ~ 120A, TiSi target uses Ti 0.8 Si 0.2 Target, TiSi target current is 120~140A, The substrate bias voltage during deposition is -120 to -100 V, and the thickness of the TiAlSiN layer (4) is 1.1 to 1.5 μm.
8. The method for preparing a hard TiAlSiN composite coating with low internal stress according to claim 2, characterized in that: The temperature of the primary cooling in step S3 is 80-100°C.
9. The method for preparing a hard TiAlSiN composite coating with low internal stress according to claim 2, characterized in that: The heating temperature in step S4 is 450-480°C. The vacuum degree of vacuum pumping is 8×10 -4 ~3×10 -3 Pa, The gas to be ionized is selected from one or more rare gases of argon, neon, and helium, and the flow rate of the gas to be ionized is 200 to 240 sccm. The bombardment substrate bias voltage is -220 to -180 V, and the time is 10 to 15 minutes.
10. The method for preparing a hard TiAlSiN composite coating with low internal stress according to claim 2, characterized in that: The first stage of the two-stage cooling in step S6 has a cooling rate of 4-6°C / min and a temperature of 200-350°C. The cooling rate of the second stage is 2-4°C / min and the temperature is 50-200°C.
Citation Information
Patent Citations
TiAlSiN coating layer preparation method based on reactive sputtering hysteresis effect
CN107227441A
Multilayer ultra-low stress hard film with alternated layer-columnar microstructures and preparation method of multilayer ultra-low stress hard film
CN115198229A